PEMAKNAAN PENGALAMAN MENULIS MAHASISWA BERGAYA BELAJAR AUDITORI STUDI FENOMENOLOGIS DI UPI KAMPUS SERANG - Deni Wardana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore and understand the writing skills of university students with auditory learning styles based on their lived learning experiences. The study employed a qualitative approach using a phenomenological method. The research was conducted at Universitas Pendidikan Indonesia, Serang Campus. The participants consisted of six university students who demonstrated an auditory learning style and had taken courses requiring academic writing skills. To ensure confidentiality, the participants were coded as M1, M2, M3, M4, M5, and M6. Data were collected through in-depth interviews and observation during writing instruction activities. The data were analyzed through data reduction, meaning categorization, thematic presentation, and essence interpretation. The findings reveal that the writing skills of students with auditory learning styles are developed through listening to verbal explanations, engaging in discussions, and speaking prior to writing. Students perceive writing as a process that begins with verbal understanding to organize ideas and structure their thoughts. Difficulties arise when writing instruction provides limited auditory activities. This study concludes that auditory learning experiences play an important role in shaping students’ writing skills and should be accommodated in university-level writing instruction.